Oxidative stress regulates autophagy in cultured muscle cells of patients with chronic obstructive pulmonary disease. Issue 12 (26th June 2018) - Gouzi, Fares; Blaquière, Marine; Catteau, Matthias; Bughin, François; Maury, Jonathan; Passerieux, Emilie; Ayoub, Bronia; Mercier, Jacques; Hayot, Maurice; Pomiès, Pascal
Abstract : The proteolytic autophagy pathway is enhanced in the lower limb muscles of patients with chronic obstructive pulmonary disease (COPD). Reactive oxygen species (ROS) have been shown to regulate autophagy in the skeletal muscles, but the role of oxidative stress in the muscle autophagy of patients with COPD is unknown. We used cultured myoblasts and myotubes from the quadriceps of eight healthy subjects and twelve patients with COPD (FEV1% predicted: 102.0% and 32.0%, respectively; p  < 0.0001). We compared the autophagosome formation, the expression of autophagy markers, and the autophagic flux in healthy subjects and the patients with COPD,  and we evaluated the effects of the 3‐methyladenine (3‐MA) autophagy inhibitor on the atrophy of COPD myotubes. Autophagy was also assessed in COPD myotubes treated with an antioxidant molecule, ascorbic acid. Autophagosome formation was increased in COPD myoblasts and myotubes ( p  = 0.011; p  < 0.001), and the LC3 2/LC3 1 ratio ( p  = 0.002), SQSTM1 mRNA and protein expression ( p  = 0.023; p  = 0.007), BNIP3 expression ( p  = 0.031), and autophagic flux ( p  = 0.002) were higher in COPD myoblasts. Inhibition of autophagy with 3‐MA increased the COPD myotube diameter ( p  < 0.001) to a level similar to the diameter of healthy subject myotubes. Treatment of COPD myotubes with ascorbic acid decreased ROS concentration ( p  < 0.001), ROS‐induced protein carbonylation ( p  = 0.019), the LC3 2/LC3 1 ratio ( p  = 0.037), the expression of SQSTM1 ( p  < 0.001) and BNIP3 ( p  < 0.001), and increased the COPD myotube diameter ( p  < 0.001). Thus, autophagy signaling is enhanced in cultured COPD muscle cells. Furthermore, the oxidative stress level contributes to the regulation of autophagy, which is involved in the atrophy of COPD myotubes in vitro. Abstract : Autophagosome formation, the LC3 2/LC3 1 ratio, autophagy‐related gene expression, and the autophagic flux are increased in chronic obstructive pulmonary disease (COPD) muscle cells. Treatment of COPD myotubes with an antioxidant molecule decreased the reactive oxygen species (ROS) concentration, ROS‐induced protein carbonylation, the LC3 2/LC3 1 ratio, the expression of SQSTM1 and BNIP3 and increased the COPD myotube diameter. The oxidative stress level contributes to the regulation of autophagy, which is involved in the atrophy of COPD myotubes in vitro.